HUBUNGAN SELF EFFICACY IBU DENGAN PEMBERIAN ASI EKSKLUSIF - Meyda, Ranita; Wijayanti, Lumastari Ajeng (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The success of exclusive breastfeeding is an important goal that is influenced by various factors, one of which is the psychological condition of the mother. A crucial factor in this case is the level of self-confidence of the mother in her ability to provide exclusive breastfeeding, which is scientifically known as Breastfeeding Self-Efficacy (BSE). A high level of BSE reflects the mother's confidence to overcome the challenges of breastfeeding and successfully provide only breast milk for the first six months of the baby's life. To examine the relationship between this self-confidence and breastfeeding practices, an observational analytical study with a cross-sectional approach was conducted. This study involved 30 breastfeeding mothers who were selected through a purposive sampling technique. Data collection used the Breastfeeding Self Efficacy Scale Short Form (BSES-SF) instrument and supporting questionnaires. The results of statistical analysis using the Spearman rank test showed a statistically significant relationship (p = 0.048). These findings confirm that the higher the level of breastfeeding self-efficacy of a mother, the greater the probability of her success in providing exclusive breastfeeding. Thus, BSE has been shown to play a fundamental role and is an important predictor of the actions and success of mothers in breastfeeding exclusively. ABSTRAKKeberhasilan pemberian Air Susu Ibu (ASI) eksklusif merupakan tujuan penting yang dipengaruhi oleh berbagai faktor, salah satunya adalah kondisi psikologis ibu. Faktor krusial dalam hal ini adalah tingkat keyakinan diri ibu dalam kemampuannya memberikan ASI secara eksklusif, yang secara ilmiah dikenal sebagai Breastfeeding Self-Efficacy (BSE). Tingkat BSE yang tinggi mencerminkan keyakinan ibu untuk mengatasi tantangan menyusui dan berhasil memberikan hanya ASI selama enam bulan pertama kehidupan bayi. Untuk mengkaji hubungan antara keyakinan diri ini dengan praktik pemberian ASI, sebuah penelitian analitik observasional dengan pendekatan cross sectional telah dilaksanakan. Penelitian ini melibatkan 30 responden ibu menyusui yang dipilih melalui teknik purposive sampling. Pengumpulan data menggunakan instrumen Breastfeeding Self Efficacy Scale Short Form (BSES-SF) dan kuesioner pendukung. Hasil analisis statistik menggunakan uji Spearman rank menunjukkan adanya hubungan yang signifikan secara statistik (p=0,048). Temuan ini mengkonfirmasi bahwa semakin tinggi tingkat breastfeeding self efficacy seorang ibu, semakin besar pula probabilitas keberhasilannya dalam memberikan ASI eksklusif. Dengan demikian, BSE terbukti memainkan peran fundamental dan menjadi prediktor penting bagi tindakan serta keberhasilan ibu dalam menyusui secara eksklusif.